(untitled) (Research, Society and Development, 2021)
Objective: to describe the knowledge of academics in the field of health about palliative care (PC), in addition to analyzing data about the students’ perception of palliative care. Methodology: Exploratory descriptive study with a quantitative approach, carried out with students from the Nursing, Pharmacy, Physiotherapy, Speech Therapy, Medicine, Nutrition, Dentistry and Occupational Therapy courses; enrolled from the 3rd cycle / year of graduation; who agreed to participate in the research. Results: The sample consisted of 254 academics, with the majority being female (65.8%). As for the cycle, 49.2% were from cycle III, 29.5% cycle IV, 17,0% cycle V; 4.3% cycle VI. Almost all participants (98.4%) reported that PC discipline was very important or important during graduation. More than 60% of academics associated palliative PCs as any measure with a curative intent, going against what the PC concepts / philosophy proposes. Conclusion: It is evident how important the approach to PC in the curriculum is, however, the gap that still exists in the undergraduate courses surveyed is also evident. It is necessary to include specific disciplines and extracurricular actions on the subject in the curricula of health courses.